PROGRAM ANTI-DOWRY OLEH UNITED NATIONS WOMEN DI INDIA TAHUN 2016-2018 - Rasyid Ridha; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study discusses the Anti-Dowry Program implemented by United Nations Women in India from 2016 to 2018. The data collection method used is a literature study, with secondary data collection from literature relevant to the problem under study, such as books, journals, newspapers, and internet sources. The research approach used is qualitative, with the aim of understanding the phenomena experienced by research subjects holistically and descriptively in the form of words. The Anti-Dowry Program aims to address the serious problem of dowry practices that are still ongoing in India. This practice has had a negative impact on gender equality, women's rights and family life. During the research period, United Nations Women has worked closely with the Indian government and various agencies to eradicate this practice. This research reveals that the Anti-Dowry Program has achieved some significant results. First, through an intensive public awareness campaign, the program succeeded in raising awareness about the issue of dowry and its adverse effects. Second, the program has strengthened laws and regulations related to dowry, thereby providing stronger legal protections for women. Keywords: Anti-Dowry, United Nations Women, India, Dowry, Gender Equality